(untitled) (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2015)
Psoriasis is a chronic, autoimmune skin disease with cutaneous manifestations; association of several factors including environmental, genetics and immunological abnormalities with psoriasis is documented. The acronym ANCA (Anti-Neutrophil Cytoplasmic Autoantibodies) is defined by an accumulation of autoantibodies with specificity against different granulocytic, monocyte and probably endothelial cytoplasmic antigens include (elastase, lactoferrin, lysozyme and Cathpsin G ), are most commonly found in systemic vasculitis, necrotizing vasculitis and in active generalized wegener’s granulomatosis. The objective of this study is to assess the anti-neutrophil antibody level (ANCA) as inflammatory markers in patients with psoriasis with different degree of severity, correlate the results with the degree of severity and compare the level of these antibodies with those of control group. This study was conducted from Feb. 2014 to Feb. 2015, blood samples were collected from thirty two persons attending to Al-Karama Teaching Hospital, Baghdad Teaching Hospital and private clinics, sixteen of them having psoriasislabelled as study groups and the rest were free of the disease labelled as control group. The psoriatic patients were classified into three groups according to the degree of severity of the disease as mild (four patients), moderate (four patients) and sever (eight patients), the Psoriasis Area Severity Index (PASI) were used to assess the severity of the disease. Thepatient’sgroup distributed as male (31.2%) and female (62.8%), the serum level of ANCA antibody was measured in thepatient’s serum of different degree of severity and in control group by using EnzymeLinked Immunosorbent Assay technique (ELISA) in laboratory of Al-karama Teaching Hospital. The results proved that the serum levels of ANCA in psoriatic patients were significantly higher than that of control group in all degree of disease severity when ANOVA test used to analyze the data, also the results reported that the level of anti- elastase and ant-lactoferrin were significantly higherin sever degree group of psoriatic patients than mild and moderate degree groups (p≤0.05)when tested by LSD test, no significant difference was noted between mild and moderate degree groups (p >0.05). From that we can conclude that autoantibodies against neutrophil antigens are generally associated with inflammatory psoriatic disorder; In addition, the autoantibodies levels were related to the degree of severity of the disease especially antielastase and antilactoferrin